Dental implications of inherited connective tissue disorders in South Africa - Chetty, Manogari (Division of Human Genetics, 2016)
The prevalence of Osteogenesis imperfecta type III (OI III) as a category of the inherited connective tissue disorders in South Africa is of paramount importance. Although worldwide, autosomal recessive(AR) OI is rare, it had emerged that the frequency of OI III is relatively high in the indigenous Black African population of South Africa. A review of the literature revealed a paucity of information regarding the dental and craniofacial manifestations of the disorder in this ethnic group. For these reasons, the central theme of this thesis is the identification, documentation and analysis of these features in individuals with OI III in the Black African population of SA. Osteogenesis imperfecta type III (OMIM 259420) is a severe autosomal recessive disorder in which frequent fractures and progressive limb and spinal deformity result in profound physical disability. The condition is heterogeneous and dentin genesis imperfecta (DI) is an important syndromic component of some types of OI III. Other maxillofacial and dental manifestations also have significant implications in terms of management.